Nanovenoms synthesis for its potential use in antisera production against rattlesnake venom (Crotalus durissus terrificus) - Baudou, Federico Gastón (2019)
Fil: Baudou, Federico Gastón. Universidad Nacional de Lujan. Departamento de Ciencias Básicas; Argentina.